Schools for Health, Education and Development : A Call for Action - Tang, K. C.; Nutbeam, D.; Aldinger, C.; St Leger, L.; Bundy, D.; Hoffmann, A. M.; Yankah, E.; McCall, D.; Buijs, G.; Arnaout, S.; Morales, S.; Robinson, F.; et al. (2012)
In 2007, the World Health Organization, together with United Nations and international organization as well as experts, met to draw upon existing evidence and practical experience from regions, countries and individual schools in promoting health through schools. The goal of the meeting was to identify current and emerging global factors affecting schools, and to help them respond more effectively to health, education and development opportunities. At the meeting, a Statement was developed describing effective approaches and strategies that can be adopted by schools to promote health, education and development. Five key challenges were identified. These described the need to continue building evidence and capturing practical experience in school health; the importance of improving implementation processes to ensure optimal transfer of evidence into practice; the need to alleviating social and economic disadvantage in access to and successful completion of school education; the opportunity to harness media influences for positive benefit, and the continuing challenge to improve partnerships among different sectors and organizations. The participants also identified a range of actions needed to respond to these challenges, highlighting the need for action by local school communities, governments and international organizations to invest in quality education, and to increase participation of children and young people in school education. This paper describes the rationale for and process of the meeting and the development of the Statement and outlines some of the most immediate efforts made to implement the actions identified in the Statement. It also suggests further joint actions required for the implementation of the Statement.